2005
DOI: 10.1007/s00239-004-0317-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Evolution of Metabolic Networks of Unicellular Translationally Biased Organisms from Transcriptomic Data and Sequence Analysis

Abstract: Abstract. Codon bias is related to metabolic functions in translationally biased organisms, and two facts are argued about. First, genes with high codon bias describe in meaningful ways the metabolic characteristics of the organism; important metabolic pathways corresponding to crucial characteristics of the lifestyle of an organism, such as photosynthesis, nitrification, anaerobic versus aerobic respiration, sulfate reduction, methanogenesis, and others, happen to involve especially biased genes. Second, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…The most prominent trend in our results is consistent with previous research [28], [33], with translational selection readily acting on genes involved in protein production and in energy metabolism. Genes that are rarely OCU are involved in regulation, DNA replication and repair, sensing of stimuli, and most kinds of transport, except the electron transport chain and ATP synthesis-coupled H + transport.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The most prominent trend in our results is consistent with previous research [28], [33], with translational selection readily acting on genes involved in protein production and in energy metabolism. Genes that are rarely OCU are involved in regulation, DNA replication and repair, sensing of stimuli, and most kinds of transport, except the electron transport chain and ATP synthesis-coupled H + transport.…”
Section: Resultssupporting
confidence: 92%
“…If organisms defined by a specific lifestyle show a tendency contrary to the general trend, and this tendency is constrained to a gene functional category, this correlation could be biologically meaningful. An example illustrative of this principle was previously brought forward in work by Karlin [40] and Carbone [28], where the glycolysis genes were claimed to be more frequently codon-optimized in anaerobic bacteria. Indeed, we detected this association (GO∶6096, enrichment = 2.1x, p  = 10 −33 ) alongside with a – not unexpected – increase in OCU frequency of carbohydrate transporters (GO∶8643, enrichment = 1.8x, p  = 10 −14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They organize in two different positional networks, which occupy distinguished chromosomal ‘facets' over the same period (Figure 5A; Supplementary Figure 8). It might appear striking that the set of genes involved in E. coli K12 metabolism is periodically organized in the same way as the set of core genes (compare violet and red curves in Figure 5A), but in fact, core genes have been used already in Carbone and Madden (2005) to identify key metabolic networks for a number of bacteria, including E. coli K12 , and to highlight that genes involved in metabolism are subject to a strong evolutionary pressure on their codon bias. Our current finding adds a new insight on our understanding of the evolutionary pressure undergoing metabolic pathways, reporting that these genes need also to preserve a regular positional distribution along the chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis of many genomes has revealed that there is a fraction of genes that show no evidence for translational selection linked to codon usage (Carbone and Madden 2005; dos Reis et al 2004; Sharp et al 2005). This observation is not supported by recent, multi-genome, studies indicating that the translational selection for codon usage seems universal, at least in prokaryotes (Hershberg and Petrov 2008; Supek et al 2010) and plastids (Suzuki and Morton 2016).…”
mentioning
confidence: 99%